Burkina Faso : School Autonomy and Accountability - World Bank (Washington, DC, 2014)
Burkina Faso has been rapidly decentralizing its education system since 2004. Although the Parents' Association (APE) is defined as the school council in this report due to its nationwide coverage, the government initiated efforts to establish school management committees (Comites de Gestion, or COGES) in 2008 as a platform for all local stakeholders to be engaged in school management. Budgetary autonomy is latent in the school system. Currently public primary schools in Burkina Faso have no autonomy over salary and non-salary expenditures. By contrast, autonomy in personnel management is established, having been delegated to the commune level in 2009. The role of the school council in school governance is also latent; it has no authority to participate in budget formulation or execution. School and student assessment is emerging: standardized tests are implemented in specific grades, with the results analyzed by the Ministry of national education and literacy and shared with its regional, municipal, and local offices. Finally, accountability is latent. There is a national and regional system to analyze standardized assessments, yet the school council has received no guidelines on how to use assessment results. Neither does the council have the authority to be involved in financial audits. Burkina Faso has dramatically improved the gross enrolment rate for primary education, from 42 percent in 1999 to 75 percent in 2009 (UNESCO 2009). School autonomy and accountability are key components of an education system that ensure educational quality. The transfer of core managerial responsibilities to schools promotes local accountability; helps reflect local priorities, values, and needs; and gives teachers the opportunity to establish a personal commitment to students and their parents. This report focuses specifically on policies in the area of school autonomy and accountability.